Cournot Retrouvé under Price or Supply Function Competition - Flavio Delbono; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This paper aims at participating in the long-lasting debate about the analytical foundations of the Cournot equilibrium. In a homogeneous oligopoly, under standard regularity conditions, we prove that Cournot-Nash emerges both under (i) price competition and Cournot conjectures; and (ii) supply function competition with ex post market clearing. We demonstrate both results within a model of exogenous product differentiation.
Keywords: D43; L13; 330